Pengaruh Suhu Terhadap pH Larutan Penyangga Dalam Optimasi Kondisi Penyimpanan di Laboratorium: Studi Parameter Uji Akreditasi ISO 17025-2107 - Marlia Novita; Firmanul Qadri Amir; Salmiati Salmiati; Yulia Eka Putri (Universitas Andalas, 2026)
Buffer solution have an essential role in ensuring pH measurement accuracy, particularly in laboratories implementing ISO 17025-2017 standards. Temperature fluctuation can cause pH changes that potentially reduce pH meter calibration accuracy and affect the quality of test results,. This study aims to analyze the effect of storage temperature on buffer pH stability and determine the optimal storage conditions,. An experimental design was employed with three storage temperature variations, namely cold (±13°C), room (±25°C), and high (±50°C), applied to pH 4, 7, and 10 buffer solutions,. Measurements were conducted every 24 hours for seven days using a digital pH meter. Data were statistically analyzed to identify significant changes and determine the optimal temperature. The results are expected to provide effective buffer storage recommendations, support chemical management in laboratories, and enhance testing reliability in accordance with ISO 17025:2017 standards.